Alimentación Saludable: ¡Organice Su Plato! - Jennifer Hillan; Linda B. Bobroff (EDIS)
FCS8796-SPAN, a 2-page fact sheet by Jennifer Hillan and Linda B. Bobroff, is the Spanish version of "Create Your Plate" (FCS8796/FY823). It explains how to do a real-life exercise with plates and food that will help consumers learn about balanced eating and portion control. Published by the UF Department of Family, Youth and Community Sciences, December 2006.